Effect Of Different Levels Of Nitrogen Phosphorus & Potassium On The Growth & Yield Of Vegetable Cowpea Var. Kurutholapayar Grown As An Intercrop In The Coconut Gardens & In The Open - Rajesh Chandran (Department of agronomy, College of Agriculture, 1987)
Field experiments were conducted at the college of Agriculture, Vellayani during 1986 to study the effect of three levels of nitrogen (10,20 30 kg/ha), three levels of phosphorus (20, 40, 60 kg P2 O5 /ha) and three levels of potassium (10,20 and 30 kg K2 O/ha) on the growth, yield and quality of vegetable cowpea Var. Kurutholapayar grown in the coconut gardens and in the open. The experiment was laid out in a 33 factorial experiment with two replications confounding NPK in replication I and NP2 K2 in replication 2. The same experiment was simultaneously laid out, both in the open and in the coconut garden. The abstract of the results is presented below. Nitrigen application upto 30 kg/ha or phosphorus application upto 60 kg P2O5/ ha increased the vine length, leaf number per plant, dry matter production, number of pods per plant and number of seeds per pod. Application of 30 kg N/ha or 60 kg P2 O5/ ha resulted in the highest uptake of nitrogen and phosphorus. The highest potassium uptake was noticed with the application of 20 kg K2 O/ ha. The fresh bhusa yield of vegetable cowpea var. Kurutholapayar increased with N application upto 30 kg/ha or P application upto 60 kg P2 O5/ha. Application of potassium had no significant effect on the fresh pod yield of vegetable cowpea in the red loam soils of vellayani containing medium amounts of potassium. A maximum net income of Rs. 11,044.80 was obtained from the plants raised in the open by the application of “30 kg N along with 60 kg P2 O5 and 30 kg K2 O/ha”. In general, vegetable cowpea grown in the open showed a much better performance compared to those raised under the partial shade.